Age-related differences in linear sprint in adolescent female soccer players - Mainer-Pardos, E.; Gonzalo-Skok, O.; Nobari, H.; Lozano, D.; Pérez-Gómez, J. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background Several studies have observed the contribution of chronological age, biological maturation, and anthropometric characteristics to sprinting performance in young soccer players. Nevertheless, there are no studies that have analysed the contribution of these characteristics to running speed qualities in adolescent female soccer players.